2018
DOI: 10.1002/qj.3246
|View full text |Cite
|
Sign up to set email alerts
|

Simple solutions for the summer shallow atmospheric circulation over North Africa

Abstract: The spring‐to‐summer shallow atmospheric circulation over North Africa is driven by two desert heat lows (DHLs), one over the Sahara (SHL) and one over Arabia (AHL), with cyclones embedded in the convective layer, capped by mid‐tropospheric anticyclones. The aim of this work is to produce a minimal theoretical framework for these dynamical features in terms of Kelvin, mixed and planetary mode solutions to a two‐layer Matsuno–Gill model with a lower Rayleigh frictional layer dynamically coupled to an almost fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Ref. [36] analyzed this circulation structure and highlighted the strengthening of the AHL in summer and its impact in terms of a vertical zonal circulation structure associating mean lift over Arabia and mean subsidence over Libya. Therefore, after various tests, we choose, following the example of the SHL, an index that we conveniently call AHL, by the geographical average of the air temperature at 850 hPa over the domain 25˚E-35˚E; 18˚N-30˚N.…”
Section: Definition Of Shl and Ahl Indexesmentioning
confidence: 99%
“…Ref. [36] analyzed this circulation structure and highlighted the strengthening of the AHL in summer and its impact in terms of a vertical zonal circulation structure associating mean lift over Arabia and mean subsidence over Libya. Therefore, after various tests, we choose, following the example of the SHL, an index that we conveniently call AHL, by the geographical average of the air temperature at 850 hPa over the domain 25˚E-35˚E; 18˚N-30˚N.…”
Section: Definition Of Shl and Ahl Indexesmentioning
confidence: 99%
“…Dalu et al [60] showed that the strength and position of SAC are tightly related to the SHL dynamics. The SHL drives a Walker-like subsiding to the west, which in turn reinforces the SAC.…”
Section: Shl and Sac Positions And Intensitymentioning
confidence: 99%